2014
DOI: 10.1515/zkri-2014-1766
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of 1-hydroxylimidazole and imidazole 1-oxide derivatives

Abstract: The N-oxide or 1-hydroxy forms of four solid 1-hydroxy-5-(4-methyl-2-nitroimidazol-2-yl)-4-phenyl-2-(Xphenyl)-imidazole derivatives, 6, have been studied by X-ray crystallography. Compounds, (6: X = 4-Br) and (6: X = 2-O 2 N), both recrystallized from EtOH, and (6: X = 4-F), recrystallized from EtOCH 2 CH 2 OH, were isolated in the 1-hydroxyimidazole form. In contrast, (6: X = H), recrystallized from EtOCH-2 CH 2 OH, was obtained in the imidazole N-oxide form. Two independent molecules, Mol A and Mol B, rotame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…18 Unambiguous evidence for the occurence of the Nhydroxyimidazole tautomeric form in the solid state may be obtained from the X-ray structural analysis data (see, e.g., papers). [19][20][21][22][23][24][25] In the report 24 the X-ray data for 1-hydroxyimidazole derivatives were considered with regard to their tautomeric form stabilization.…”
Section: Synthesis and Study Of Prototropicmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Unambiguous evidence for the occurence of the Nhydroxyimidazole tautomeric form in the solid state may be obtained from the X-ray structural analysis data (see, e.g., papers). [19][20][21][22][23][24][25] In the report 24 the X-ray data for 1-hydroxyimidazole derivatives were considered with regard to their tautomeric form stabilization.…”
Section: Synthesis and Study Of Prototropicmentioning
confidence: 99%
“…One of the most widespread and convenient methods to synthesize 1-hydroxyimidazoles is a cyclization of starting aldehydes with α-hydroxyiminoketones and ammonium acetate 1,2,4,7,23,24,[26][27][28][29][30] in alcohols or glacial acetic acid. Scheme 2.…”
Section: Synthesis Of Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant form of 1-hydroxy-1 H -imidazoles, N -hydroxyl or N -oxide, depends on the proton-donating or proton-accepting properties of the media, substituents in the imidazole ring and packing of the molecules in the solid state. 90–98…”
Section: Introductionmentioning
confidence: 99%
“…The predominant form of 1-hydroxy-1H-imidazoles, N-hydroxyl or N-oxide, depends on the proton-donating or proton-accepting properties of the media, substituents in the imidazole ring and packing of the molecules in the solid state. [90][91][92][93][94][95][96][97][98] In the case of 1-hydroxy-1H-imidazoles, this strategy can purposedly be interwoven with the strategy of the rational design of ESIPT-ligands for the synthesis of ESIPT-capable metal complexes. We suggested that coupled with the ease of the deprotonation of the hydroxy group, the introduction of a suitable proton accepting moiety in position 2 or 5 of the imidazole cycle could promote not only the intramolecular proton transfer from the 1-hydroxy group to this nearby proton accepting group, but also leave the N 3 imidazolic atom free for metal coordination.…”
Section: Introductionmentioning
confidence: 99%